Mating behaviour and breeding of the grey bamboo shark, Chiloscyllium griseum Müller & Henle, 1838 in captivity - Anandhakumar, C.; Dhinakar Raj, Gopal; Uma, Arumugam; Thirumurugan, Krishnaswamy Gopalan; Raja, Angamuthu; Kumanan, Kathaperumal (Indian Journal of Fisheries, 2012)
In the present study, the mating behaviour and breeding of the grey bamboo shark (Chiloscyllium griseum), in captivity wasdocumented. During mating, two male sharks grasped the pectoral fins of one female, with the dominant male succeeding incopulation in a vertical position. Subsequently, 22 eggs cases were laid in pairs of which 7 eggs hatched after a period of 114-125 days with 85.7% survival. The male to female sex ratio in shark pups was 1:0.75. In India, this is the first report ofcomplete documentation of the mating behaviour and breeding of sharks in captivity.